ARAHAN PENGEMBANGAN KOMODITAS UNGGULAN PERTANIAN TANAMAN PANGAN DI KABUPATEN BOVEN DIGOEL PROVINSI PAPUA - Keratorop, Marianus; Widiatmaka, Widiatmaka; Suwardi, Suwardi (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2016)
Economic characteristic of The Boven Digoel Regency is dominated by agriculture. Food crops has an important role in agricultural and economic development in Boven Digoel Regency. The objectives of this paper are : (1) Identifying and establishing food crops as the superior commodities, (2) Delineating the land availability for superior food crops development, (3) Assessing land suitabilityof superior food crops commodities and (4) Arranging direction development of superior food crops commodities in Boven Digoel Regency. The methodology used in this paper were consisted of the analysis of Location Quotient (LQ), Shift Share Analysis (SSA), and evaluation of the land availability and land suitability. Results of LQ and SSA analyzes showed that cassava, sweet potato, paddy, corn and peanuts are the superior food crops commodities. The results of analyzes of land availability are presented in three scenarios. In the first scenario, available land covers an area of 36.227 ha, in the second scenario available land covers an area of 43.401 ha, while in the third scenario, available land covers an area of 610.990 ha. Evaluation of the suitable land in available land indicated that most of the land include in S3 class (marginally suitable), whilew the least area include in N class (not suitable). The developments of food crops in Boven Digoel were then done by considering the suitable and available land as well as comparative and competitive advantage of the comodities.